Personality differences between birth order categories and across sibship sizes - Michael C. Ashton; Kibeom Lee (Proceedings of the National Academy of Sciences, 2025)
We examined associations of self-reports on the HEXACO Personality Inventory—Revised (HEXACO-PI-R) with birth order category and sibship size, controlling for participant sex and age. In a first sample ( N > 700,000 online adults, mainly from English-speaking countries), Honesty-Humility and Agreeableness both showed the highest means for middle-borns, followed in order by last-borns (youngests), firstborns (oldests), and only children, with differences between middles and onlys of d ≥ 0.20. The same result was replicated in a similar but smaller second sample ( N > 70,000) in which sibship size was also assessed, thereby allowing birth order differences to be separated from sibship size differences. In that sample, Honesty-Humility and Agreeableness showed higher means with larger sibship sizes, with differences between sibship sizes of 1 and 6+ of d = 0.30 and d = 0.36, respectively. Controls for upbringing religiousness and current religiousness reduced these differences by about 25%. Within sibship sizes, birth order differences in these dimensions were considerably smaller but oldests remained up to d = 0.10 lower than middles and youngests. Openness was d ≈ 0.10 higher for onlys than for non-onlys collectively, and within sibship sizes, Openness was d ≈ 0.10 higher for oldests than for middles and youngests.